Reporte de Peridiniopsis borgei Lemmermann (Dinophyceae) en aguas continentales de Perú - Ascencio, Enrique; Mendoza, Leonardo; Baylón, Maribel; Rivera, Patricio; Krakhmalnyi, Aleksander F.; Cruces, Fabiola; Urrutia, Roberto (Gayana Botánica, 2020)
We reported the presence of Peridiniopsis borgei Lemmermann in La Encantada lake (Province of Huaura) and studied the specimens using optical and scanning electron microscopical techniques. The population of P. borgei showed a variation in the number and degree of development of the marginal ridges. This is the first illustrated report of the species in Perú.